Capital Structure, Firm Size, to Financial Performances in Indonesian property and real estate companies - Nuraini, Miranda; Hidayatullah, Siti Rahmi; Sinurat, Honesty (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The main goal of this study is to examine the impact of capital structure, the size of the company to financial performance. This study uses data from property and real estate companies listed on the Indonesia Stock Exchange between 2022 and 2023. The dependent variable used is the return on Equity (ROE). The independent variables are Debt to assets (DAR), debt to equity ratio (DER), and company size (FS). This study uses purposive sampling as the sampling technique. This study had 68 samples that met the sample criteria determined by the researchers. The data analysis method used is the regression analysis method. The results showed: (a) DAR Variable may have financial performance of real estate and subsector companies for real estate listed on the Indonesia Stock Exchange between 2022-2023. (b) This variable may have a positive and significant impact on the financial performance of real estate and real estate subsector companies listed in 2022-2023. (c) FS variables have a positive and significant impact on the financial performance of real estate and subsector companies for real estate listed between 2022 and 2023.